Kepemimpinan transformasional, kualitas kehidupan kerja, dan organizational citizenship behavior: Motivasi kerja sebagai mediasi - Desi Tri Kurniawati; Meily Margaretha (Universitas Kristen Maranatha, 2024)
This research aimed to investigate the direct and indirect impact of transformational leadership and quality of work life on organizational citizenship behavior OCB, with work motivation as a mediator. An explanatory method was adopted to examine the relationship between antecedent, mediator, and consequences, with seven hypotheses being tested. A total of 216 employees from the St. Regis Hotel in Bali were selected as the participants using a simple random sampling. Data were analyzed using SEM-PLS, which included conducting validity and reliability tests through algorithm methods, followed by hypothesis testing using bootstrapping. The results of the analysis showed that transformational leadership directly impacted OCB. When work motivation acts as a mediator, transformational leadership significantly affects OCB. While QWL did not directly affect increasing OCB, its relationship with OCB became significant when work motivation was introduced as a mediator.